A Corpus-Based Critical Discourse Analysis of Indonesian Presidential Candidates’ Political Ideologies in the Mata Najwa Talk Show - Devita Hapsari Salsabila; Nurhayati Nurhayati (Dinasti Publisher, 2025)
This research analyzes the classification of words related to social and political issues used by three Indonesian presidential candidates in the “3 Capres Adu Gagasan” talk show on Najwa Shihab’s YouTube channel. The study involves transcribing the candidates’ speeches, tokenizing the text, assigning Part-of-Speech (POS) tags using the CQPWeb corpus, and generating frequency lists. The findings reveal significant differences in prioritizing social and political issues among the candidates. AB emphasizes justice and equality, PS focuses on economic development and national defense through human resource empowerment, while GS highlights social harmony and unity. Further analysis using Teun A. van Dijk's Critical Discourse analysis model uncovers each candidate’s underlying ideology: social justice (AS), economic independence and defense (PS), and social harmony (GP). The candidates’ speeches reflect their perceptions of societal realities and the values they consider important to the Indonesian public.